Determination of Cobalt in Tap Water by Deep Eutectic Solvent-Dithizone Assisted Liquid Phase Microextraction (LPME) Preconcentration with Flame Atomic Absorption Spectrometry (FAAS) - Agbulak, Asli; Kilinc, Yagmur; Zaman, Buse Tugba; Gover, Tugce; Atakol, Melike; Turak, Fatma; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2026)
This study aimed to develop an analytical method for preparing samples to preconcentrate cobalt from water in advance for determination using flame atomic absorption spectrometry (FAAS). The aforementioned outcome was attained through the complexing of cobalt ions with dithizone (Co-DTZ) and subsequently extracting the resulting complex from aqueous solution using a deep eutectic solvent (DES). The DES/DTZ probe was used as a complexing and extracting agent in the developed liquid phase microextraction (LPME) procedure. The most suitable experimental conditions were determined for the highest extraction efficiency. Consequently, 8.0 mL of standard/sample solution was adjusted to pH 6.0 using 1.0 mL of phthalate buffer. 250 mu L of the DES/DTZ probe (10 mL DES: 5.0 mg DTZ) was added to the aqueous solution to extract cobalt with the best efficiency. The DES/DTZ-LPME-FAAS system achieved a detection limit of 9.6 mu g/L with a wide linear working range between 30 and 500 mu g/L by applying the optimum procedure. The relative standard deviation of the proposed method was 6.9% for a 30 mu g/L cobalt standard. Spike recovery experiments were conducted with tap water to evaluate the accuracy and feasibility of the developed method. By performing matrix matching, the results demonstrated good recoveries from 90% to 112%.
Keywords: Cobalt; deep eutective solvent; dithizone; flame atomic absorption spectrometry (FAAS); liquid phase microextraction (LPME); SAMPLES; NICKEL; IONS; Chemistry